Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1055/a-0984-5929
|View full text |Cite
|
Sign up to set email alerts
|

Störung des Sozialverhaltens und Antisoziale Persönlichkeitsstörung - Herausforderungen in der Transition vom Jugend- zum Erwachsenenalter

Abstract: ZusammenfassungAggressives Verhalten ist ein häufiges Phänomen in der Kindheit und Jugend. Es ist auch ein häufiger Anlass für eine Behandlung in der Kinder- und Jugendpsychiatrie und psychotherapie. Störungen des Sozialverhaltens bergen ein hohes Risiko für eine lebenslange Problematik, auch für das spätere Auftreten komorbider Suchterkrankungen oder affektiver Störungen. Die Behandlung im Übergang zum Erwachsenenalter ist schwierig, weil zum einen oft die Einsicht bei den Betroffenen in die Probleme und lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Moreover, follow-up acceptance of scientific assessments was low. In line with the well-known difficulty to reach this group (e.g., [ 10 ]), collaboration with several treatment centers which can already access recruitment networks is recommended for future trials to reach a sample size large enough to detect treatment effect with sufficient power. Follow-up assessments might need an extra personal appointment and additional financial reimbursement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, follow-up acceptance of scientific assessments was low. In line with the well-known difficulty to reach this group (e.g., [ 10 ]), collaboration with several treatment centers which can already access recruitment networks is recommended for future trials to reach a sample size large enough to detect treatment effect with sufficient power. Follow-up assessments might need an extra personal appointment and additional financial reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…While psychological interventions have shown to be effective in treating youth with conduct problems (overview, e.g., in [ 8 ]), especially adolescents from middle adolescence and older are underrepresented in effective treatment programs (e.g., [ 9 ]). Treatment programs and scientific investigations for this group are still scarce (e.g., [ 10 ]). In Germany, a large-scale study on the diagnoses of youth receiving outpatient psychotherapy revealed that despite its prominent rank in prevalence in the general population [ 1 ], CD was only the seventh common psychiatric diagnosis in youth receiving outpatient psychotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zahlreiche Experten haben sich darin intensiv mit allgemeinen und störungsspezifischen Fragen zu den bestehenden Transitionslücken auseinandergesetzt und Lösungen und Empfehlungen hinsichtlich der Versorgung, Forschung und fachlichen Qualifizierung formuliert. n den folgenden Beiträgen dieses Heftes werden von der Task-Force Transitionspsychiatrie sowohl setting-bezogene [2][3][4] und störungsspezifische Aspekte [5][6][7][8] diskutiert sowie bestehende Versorgungsangebote dargestellt [9]; in allen Arbeiten werden die jeweiligen Transitionslücken identifiziert, und inhaltliche therapeutische und strukturelle Empfehlungen für das Versorgungssystem, inklusive Ansätze zum Transitionsmanagement, abgeleitet.…”
unclassified